The relative importance of type of education and subject area : empirical evidence for educational decisions - Pfister, Curdin [Verfasser]; Tuor Sartore, Simone N. [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2017)
"The purpose of this paper is to provide empirical evidence for individual educational investment decisions and to investigate the relative importance of two factors, the type of education (vocational vs. academic) and subject area (e.g., commercial or health), in determining variance in earnings. Using a sample of 1200 individuals based on the 2011 Swiss Adult Education Survey, Mincer-type earnings equations are estimated. [This sample consists of employed individuals between 25 and 64 years old. These individuals have finished their educational careers and are part of the workforce, i.e. they are neither retired nor unemployed.] The variance in earnings is decomposed with respect to the two factors mentioned above, which allows to quantify the relative contributions of type of education and subject area to variance in earnings. The results of the variance decomposition show that subject area explains nearly twice the variance in earnings compared with that explained by type of education." (Authors' abstract, BIBB-Doku)
Working Paper Version erschienen u.d.T. "Earnings Returns to Different Educational Careers: The Relative Importance of Type vs. Field of Education" (2015), http://repec.business.uzh.ch/RePEc/iso/leadinghouse/0107_lhwpaper.pdf
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.2.1 Westeuropa; Erwerbstätiger; Einkommen; Einflussfaktor; Bildungsabschluss; Ausbildungsabschluss; Studienabschluss; Ausbildungsbereich; Studienfach; Schweiz